Repositioning of the taxa at or above families of Digenea found in Vietnam based on the current classification system - Doanh, Pham Ngoc; Ha, Nguyen Van (Academia Journal of Biology, 2017)
In class Trematoda, subclass Digenea is a large and diverse subclass consisting of about 80 families with 18,000 nominal species. Classically Skrjabin divided Digenea into 20 orders. Recently, however, Digenea was simply divided into three orders and are keyed down directly to the superfamily level using morphological features of the sexually mature adults in the series monograph, Keys to the Trematoda (Vol. I 2002, Vol. II 2005, Vol. III 2008 CABI Pub). More recently, with consideration of the molecular taxonomic data, Digenea was splitted into two orders: order Diplostomida Olson, Cribb, Tkach, Bray & Littlewood, 2003 and order Plagiorchiida La Rue, 1957. In Vietnam, Skrjabin’s old classification system has still been used for the classification of Digenea, and the potision of taxa at or above the family level does not fit with the current classification system In this paper, we will collate the Digenean families found in Vietnam based on the current systematics. Citation: Pham Ngoc Doanh, Nguyen Van Ha, 2017. Repositioning of the taxa at or above families of Digenea found in Vietnam based on the current classification system. Tap chi Sinh hoc, 39(2): 133-143. DOI: 10.15625/0866-7160/v39n2.8891 *Corresponding author: pndoanh@yahoo.com Received 21 November 2016, accepted 20 March 2017